Investigation of the contribution of exchange mechanisms to the elastic scattering 10 B on the nucleus 12 C - Морзабаев, А.К.; Ергалиулы , Г.; Амангелді , Н.; Бозтосун , И.; Мәуей , Б.; Болат , Н.; Тәңірберген , А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The analysis of the experimental data on the differential cross sections for the elastic scattering of 10 B ions on 12 C nuclei at an energy of 18 MeV was carried out in the framework of the optical model (OM) and the distorted wave method (FRDWBA) using the FRESCO code. The optical model describes well the experimental cross sections in the region of the angles of the forward hemisphere, but is not able to reproduce the observed rise of the cross sections at large angles. Only accounting for the exchange mechanism with deuteron transfer allows us to describe the experiment in the full angular range. Spectroscopic amplitude has been extracted from the analysis for the configuration 12 C → 10 B+d.